Graduates who are the urban poor - Abdullah, Sholehah; Ismail, Fathiyah; Hamzah, Siti Fatimah Mardiah; Azlan, Nik Noor Afizah; Mohamad Azmin, Nur Azwani; Abdul Manaf, Suhaily Maizan; Affandi, Salwani (Fakulti Pengurusan Perniagaan, UiTM Terengganu, 2023)
Did you know that even if they are an officers or executives, graduates with a bachelor's degree earn only in between RM1,100 to RM2,200 on average per month? This is a regular scenario that new graduates experience in their professional lives these days. When these students graduate and move out into the real world, they become urban poor, even though they are highly educated. Every year, thousands of graduates are produced in the country however they have added to urban poverty. These graduates’ wages are essentially the same as those without a degree or diploma at this moment. In fact, some of them have less than those who have a high school diploma or a certificate. An officer but only earns RM1.100 each month? This means they have entered the hardcore poor group. Even security guard, for example, are paid more than that.